2017
DOI: 10.1080/16549716.2017.1305814
|View full text |Cite
|
Sign up to set email alerts
|

Explaining mental health inequalities in Northern Sweden: a decomposition analysis

Abstract: Background: There has been a substantial increase of income inequalities in Sweden over the last 20 years, which also could be reflected in health inequalities, including mental health inequalities. Despite the growing body of literature focusing on health inequalities in Sweden, income-related inequalities in mental health have received little attention. Particularly scarce are research from Northern Sweden and examinations of the social determinants of health inequalities.Objectives: The present study seeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Except for the Mazandaran site, the E for all sites had negative sign, suggesting a higher concentration of poor mental health in socioeconomically disadvantaged people. This is in line with the previous reports around the world [24][25][26]. However, the different methods employed for inequality measurement in various studies made the comparison of the concentration indices difficult.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Except for the Mazandaran site, the E for all sites had negative sign, suggesting a higher concentration of poor mental health in socioeconomically disadvantaged people. This is in line with the previous reports around the world [24][25][26]. However, the different methods employed for inequality measurement in various studies made the comparison of the concentration indices difficult.…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted by Morasae et al (2012) in Tehran, demonstrated a contribution of 13.1% for age to socioeconomic inequality in mental health in Tehran, Iran [26]. In contrast with a study by Amroussia et al [24], marital status had a small contribution to socioeconomic inequalities in poor mental health in Iran. Married people (compared to single, divorced and widowed) were found to have more contribution to socioeconomic inequality in poor mental health.…”
Section: Discussionmentioning
confidence: 75%
“…The strengths of this study include a large representative sample of Australian children, the use of comprehensive questionnaires to collect the social data, the adequate examiner reliability measures for caries measures, the use of sophisticated socioeconomic inequalities measures, and the undertaking of a multilevel analysis taking individual and contextual socioeconomic factors into account as recommended (Singh et al 2018). In addition to that, we performed decomposition analyses, which are rarely found in dental literature but increasingly used in public health (Lauridsen et al 2006;Sözmen et al 2012;Amroussia et al 2017). The main limitation of the study was the cross-sectional design.…”
Section: Improving the Pattern Of Dental Visitsmentioning
confidence: 99%
“…Second, we use the SAH, a multidimensional and more encompassing measure of health [3,5]. Third, with the exception of [22][23][24] most of the empirical studies have not measured the degree to which the covariates contribute to disparities. While gender differences in the distribution of health risk factors might contribute to gender inequalities in health status, it is also possible that these characteristics have differential effects on health risk for men and women.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used an extension of the Oaxaca-Blinder decomposition for non-linear models to investigate the relative contributions of variations in the distributions of health status versus their differential effects in producing gender inequalities in health status in Liberia [27,28]. Again, the recent few studies that have analysed the contribution of covariates to the health inequalities are mostly concentrated in developed countries [22,23] and little is known in developing countries [24]. This knowledge is crucial for designing more effective health policies and programmes in developing countries.…”
Section: Introductionmentioning
confidence: 99%